Design and Analysis of High Voltage to 48V DC-DC Converter Topologies for Automotive Applications - Arumugam, Brihadeshvaran (My University, 2024)
Abstract In automotive applications, below 60V DC operation is considered a low-voltage system, meeting safety protection requirements easily. Compared to current 12V systems, 48V systems increase efficiency by reducing currents, which allows for smaller wire sizes and higher power capability. Though 48V systems provide the abovementioned advantages, it is critical to investigate the impact of various topologies and modulation techniques on DC-DC converter efficiency. In this thesis work, based on qualitative analysis, the selected topologies are full bridge DC-DC secondary centre tap topology and full bridge DC-DC secondary side full bridge rectifier topology, which were compared with phase shift modulation and duty cycle modulation techniques. The Phase Shifted Full Bridge(PSFB) secondary side full bridge rectifier topology was then chosen to be optimized to evaluate its efficiency to the Dual Active Bridge(DAB) with its chosen modulation approaches based on various modulation comparisons. From all analyses, the Phase Shifted Full Bridge(PSFB) observes extremely high turn-off voltage oscillations across the MOSFETs on the secondary side, making it impractical to control the oscillations with a snubber and active clamping which makes it weakens the opportunity to further optimize it. As a result, it was decided to stop optimizing the PSFB. Consequently, the focus shifted to the Dual Active Bridge (DAB), which demonstrated better performance under varying loads. Operating under Extended Phase Shift Modulation(EPS) from 3750W to 1000W, it achieved an average efficiency of 92 %. Below 1000W, the implementation of Triangular Current Modulation(TRG) further improved efficiency to an average of 94 %. This performance made the DAB a more viable and efficient solution for the intended application, justifying its selection over the PSFB. While the DAB’s performance is promising and can be optimized further, concerns remain regarding high RMS and peak currents, which may result in significant copper loss in the circuit and Printed Circuit Board (PCB), and unreliable soft switching. The key limitation for high RMS and peak currents is a large input voltage range, leading to a lower turns ratio for the 48V application.
Keywords: Keywords: Dual Active Bridge, Extended Phase Shift, Phase Shift Full Bridge, Triangular Current Modulation, Snubber, Active Clamp, transformer, switch, Zero Voltage Switching, efficiency